TINJAUAN KRIMINOLOGI TINDAK PIDANA PEMALSUAN UANG (Studi Putusan Nomor 1266/PID.B/2023/PN.MDN) - Lestari, Utami Ida; Sitompul, Rina Melati (Law Jurnal, 2023)
Money is central to society's economic life as a means of transactions and settlement of obligations. However, the negative impact of the increase in counterfeiting crimes is not only detrimental to individuals in society but can also disrupt the economic stability of a country. This research aims to identify the factors that influence the criminal act of circulating counterfeit money, understand the judge's considerations in making decisions regarding the case and analyze the illegal law policies implemented in prevention efforts. The research method used is a normative juridical approach with case studies. Number 1266/Pid.B/2023/PN.Mdn. The findings of this research indicate that the influencing factors involve economic aspects, technological environment, and education. The judge's consideration in the decision refers to juridical, philosophical and sociological aspects. The criminal law policies related to the circulation of counterfeit money include regulations in the Criminal Code and Law No. 7 of 2011. The hope is that these findings can provide a holistic view regarding preventing the circulation of counterfeit money and become an essential reference in the development of criminal law science.